2020
DOI: 10.1002/pd.5618
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution analysis of the human placental DNA methylome in early gestation

Abstract: Background/Objective We communicate high‐read‐depth bisulfite sequencing analysis of the chorionic villus (CV) DNA methylome from samples obtained between 11 and 13 weeks gestation and samples of gestationally age‐matched maternal blood cells (MBC). Methods This was achieved through solution‐phase targeted region capture (84 Mb) of bisulfite converted human DNA. Results We identified biphasic distribution of methylation in CV and MBC genomes. We found greater numbers of intermediate methylated sites (20%‐80% m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…These results further demonstrate that the genomic location of CpG sites influences the maternal plasma methylome in early gestation. The fact that these gene regulatory element–containing regions are less likely to be hypomethylated in the plasma of pregnant women than structural genomic elements (exons/introns) is consistent with previous epigenomic analyses of early‐gestational CV samples and age‐matched maternal leukocytes (MBC) in which it was shown that although the CV genome is generally hypomethylated relative to MBC, it contains regions that cluster within CGIs, CGI shores, and enhancers that are relatively more methylated 35 …”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…These results further demonstrate that the genomic location of CpG sites influences the maternal plasma methylome in early gestation. The fact that these gene regulatory element–containing regions are less likely to be hypomethylated in the plasma of pregnant women than structural genomic elements (exons/introns) is consistent with previous epigenomic analyses of early‐gestational CV samples and age‐matched maternal leukocytes (MBC) in which it was shown that although the CV genome is generally hypomethylated relative to MBC, it contains regions that cluster within CGIs, CGI shores, and enhancers that are relatively more methylated 35 …”
Section: Resultssupporting
confidence: 88%
“…Given the apparent influence of the CV methylome on cfDNA methylation patterns in maternal plasma, we sought to determine whether specific loci that are known to have distinct epigenetic signatures in the CV genome may influence maternal plasma DNA methylation profiles in a predictable fashion. Such loci were identified from a previously published 35 comparison of CpG methylation between early‐gestational CV tissue samples (11‐13 weeks) and gestational age–matched MBCs 35 . These assays were performed using solution‐phase hybridization followed by bisulfite DNA sequencing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation